Screening of Bacillus for the development of bioprotectants for the control of Fusarium oxysporum f. sp. vasinfectum and meloidogye incognita - Guimarães Pacifico, Marina [UNESP] (2021)
Fusarium oxysporum f. sp. vasinfectum and Meloidogyne incognita cause large losses in cotton productivity. These pathogens can occur simultaneously, resulting in a Fusarium-nematode complex, which strengthens the destructive power when compared to the pathogens alone. Due to the ineffectiveness of chemicals, and to the fact that chemicals pesticides are responsible for releasing residues into the environment, more attention has been given to biocontrol. Bacillus are recognized by their ability to control plant-parasitic pathogens. However, since Fusarium and Meloidogyne often occur simultaneously, and the resulting complex causes more losses than each pathogen alone, selecting bioagents that act against both pathogens simultaneously is important, and this is the objective of this study. Among 40 Bacillus strains obtained from cotton rhizosphere and other sites, the most efficient ones were selected to inhibit mycelial growth and spore germination of Fusarium, cause J2 mortality and inhibit hatching of M. incognita. Forty Bacillus strains were evaluated both through biochemical tests related to plant growth promotion (indoleacetic acid, siderophores, and cyanhydric acid production; catalase activities; nitrogen fixation and phosphate solubilization) and root colonization. Strains S2531, S2535, S2545, S2548, S2552, S2554, S2555, and S2557 showed >4 positive responses for biochemical tests. Strains S2527, S2535, S2538, S2545, S2573, AP03, AP115, AP117, AP210, QST713 colonized cotton roots. Strains S2535, S2543, S2545, S2557, S2560, S2564, AP03, AP10, AP115, and AP117 inhibited mycelial growth of Fusarium. The most efficient strains for the inhibition of microconidia germination were S2545, S2548, AP115, AP03, and S2543. Strains AP117, S2527, S2530, S2538, S2560, and S2569 showed the highest mortality of J2. Strains S2527, S2557, S2569 and AP03 were the ones with the lowest area under hatching progress curve. Overall, strains AP03, S2527 and S2545 were selected to evaluate the control of the complex Fusarium-nematodes in cotton plants. These three strains were identified as Bacillus velezensis.